Effects of Organophosphorus and Pyrethroid pesticides on antioxidant enzymes and reactivation effects of Pralidoxime: In vitro studies - Hatice Paluzar; Ayten Sagiroglu (Kuwait Journal of Science)
The aim of this work was to investigate the inhibition effects of some organophosphate and pyrethroid pesticides on antioxidant enzymes. In addition, oximes were reported by reactivation ability against pesticide inhibited-acetylcholinesterase and we focused to investigate the reactivation effect of pralidoxime against organophosphate inhibited–antioxidant enzymes. This study was conducted to determine the in vitro effects of pyrethroid pesticides (deltamethrinR, λ-cyhaloethrinR) and organophosphate pesticides (malathionR, dichlorvosR) on antioxidant enzymes (catalase, superoxide dismutase, glutathione peroxidase). IC50 values were determined by means of activity percentage diagrams. Reactivation effect of pralidoxime was determined for organophosphate inhibited-enzymes. The concentrations of deltamethrinR, malathionR, dichlorvosR, λ-cyhaloethrinR that inhibited 50% of catalase were 5.2 µM, 158 µM, 133 µM, 320 µM, respectively, inhibited 50% of superoxide dismutase were 62 µM, 240 µM, 328 µM, 2320 µM, respectively  and inhibited 50% of glutathione peroxidase were 0.7 µM, 1198 µM, 1638 µM, 98 µM, respectively. Additionally, only catalase is reactivated by pralidoxime against dichlorvosR and malathionR. Deltamethrin was found to be a more potent inhibitor for the antioxidant enzymes followed by the rest of pesticides used in this study. Only organophosphate inhibited-catalase is reactivated by pralidoxime.